Barrier film, quantum dot film and preparation method thereof
By adopting a double-sided barrier film structure and efficient preparation method, the problems of limited thickness of the quantum dot film barrier layer and pinhole gap in the prior art are solved, and stronger barrier performance and longer quantum dot service life are achieved.
Patent Information
- Application Number
- CN202411987013.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
AI Technical Summary
The use of single-layer barrier layers in existing quantum dot films is prone to pinhole gap problems, the thickness of the coating is limited, the degree of protection of quantum dots is limited, and the stiffness is insufficient, and the water and oxygen barrier performance is poor, resulting in quantum dot damage and loss of function.
The barrier coating is prepared by PVD or CVD to improve barrier performance by using a double-sided barrier film structure, including a substrate and a barrier coating on one surface of the substrate and a back coating on the other surface of the substrate.
The barrier performance of the barrier film is enhanced, and the local failure problem caused by scratching the barrier film during the production process of the quantum dot film is reduced. The pinhole failure problem due to the arrangement of the plated atoms is eliminated. The service life of the quantum dots is extended and the performance stability is improved.
Smart Images

Figure CN119735850A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of liquid crystal displays, and in particular to a barrier film, a quantum dot film and a preparation method thereof. Background Art
[0002] At present, direct backlight has become a direct application of high-end display products. The design of mini-led displays has a stronger light intensity, and the dense distribution of blue light chips causes a higher temperature in the cavity. In the reality of pursuing higher brightness and better color gamut, the solution of blue light mini-led plus quantum dot film is the best form of mass production. The quantum dot display technology is that blue light excites quantum dots to produce red and green light, which are then combined with blue light to form three primary colors and then mixed into white light on the light output surface.
[0003] Because the size of quantum dots is at the nanometer level, the material itself is extremely sensitive to strong light, high heat, water and oxygen. In this harsh environment, it is very easy to quench the fluorescence and lose its function. It needs to be protected to extend its life. Barrier film blocks water and oxygen to provide a safe environment, which is currently the best way to protect it.
[0004] In the prior art, a single-layer barrier layer is used in the quantum dot film, which is prone to pinhole problems, and the coating thickness is limited, which limits the degree of protection for the quantum dots. At the same time, the single-layer barrier layer is prone to insufficient stiffness and rigidity, poor water and oxygen barrier properties, and quantum dot damage.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the objectives of the present invention is to provide a barrier film, aiming to solve at least one of the above-mentioned technical problems in the prior art.
[0007] A second object of the present invention is to provide a quantum dot film.
[0008] A third object of the present invention is to provide a method for preparing a quantum dot film.
[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0010] A first aspect of the present invention provides a barrier film, including a single-sided barrier film and / or a double-sided barrier film;
[0011] The single-sided barrier film comprises a substrate and a barrier coating located on one surface of the substrate;
[0012] The double-sided barrier film comprises a substrate, a barrier coating layer located on one surface of the substrate, and a back coating layer located on the other surface of the substrate.
[0013] Furthermore, the barrier coating or the back coating is obtained by PVD or CVD.
[0014] Furthermore, the substrate includes polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polymethyl methacrylate, polylactic acid or polyester polyurethane, preferably polyethylene terephthalate.
[0015] Preferably, the material of the barrier coating includes at least one of SiOx, SiNx, SiCx and ZrOx, wherein 0<x≤2.
[0016] Preferably, the back coating layer is formed by coating with back glue.
[0017] Preferably, the back-coated glue includes resin and organic / inorganic particles.
[0018] Preferably, the resin comprises UV type acrylic resin.
[0019] Furthermore, the thickness of the substrate is 12 to 150 μm.
[0020] Preferably, the thickness of the barrier coating is 100-200 nm.
[0021] Preferably, the back coating layer has a thickness of 2 to 10 μm.
[0022] A second aspect of the present invention provides a quantum dot film, comprising a first barrier film group, a quantum dot glue layer and a second barrier film group stacked in sequence.
[0023] The first barrier film group and the second barrier film group include at least one layer of the barrier film.
[0024] Furthermore, the quantum dot glue layer contains quantum dots.
[0025] Preferably, the quantum dots include red quantum dots and green quantum dots.
[0026] Furthermore, the wavelength of the red quantum dots is 620-634 nm.
[0027] Preferably, the wavelength of the green quantum dots is 528-539 nm.
[0028] Furthermore, the first barrier film group includes a double-sided barrier film and a single-sided barrier film.
[0029] Preferably, the number of layers of the single-sided barrier film is 0 to 3.
[0030] Preferably, the double-sided barrier film is located at the outermost side of the first barrier film group.
[0031] Furthermore, the second barrier film group includes a double-sided barrier film and a single-sided barrier film.
[0032] Preferably, the number of layers of the single-sided barrier film is 0 to 3.
[0033] Preferably, the double-sided barrier film is located at the outermost side of the second barrier film group.
[0034] The third aspect of the present invention provides a method for preparing the quantum dot film, comprising the following steps:
[0035] A. Use a bonding adhesive to bond the barrier films in the first barrier film group and the second barrier film group together, and after curing, obtain the first barrier film group and the second barrier film group respectively.
[0036] B. Applying quantum dot glue between the first barrier film group and the second barrier film group, and UV curing to obtain the quantum dot film.
[0037] Furthermore, the bonding adhesive includes UV bonding adhesive, thermosetting bonding adhesive or mixed bonding adhesive, preferably thermosetting bonding adhesive.
[0038] Preferably, the lamination method includes roller lamination.
[0039] Preferably, in step B, the coating method is slit coating.
[0040] Preferably, in step B, during the UV curing, the energy is 150-600 mj / cm.
[0041] Compared with the prior art, the present invention has at least the following beneficial effects:
[0042] The barrier film provided by the present invention has stronger barrier properties. Without affecting other properties, it can reduce the problem of local failure caused by scratches on the barrier film during the production process of the quantum dot film, and eliminate the pinhole failure problem caused by the atomic arrangement of the coating. The overall barrier performance is improved, the protection of quantum dots is enhanced, and the service life is extended.
[0043] The quantum dot film provided by the present invention, in view of the advantages of the above barrier film, enables the prepared quantum dot film to have a longer service life and performance stability. This technical solution enables the quantum dot film to have significant application advantages and broad market prospects in the field of display technology.
[0044] The method for preparing the quantum dot film provided by the invention has simple process, high mechanization degree and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0046] Figure 1 This is the structure diagram of α-quartz SiOx;
[0047] Figure 2 This is the structure diagram of β-quartz SiOx;
[0048] Figure 3 A structural diagram of the quantum dot film provided by the present invention;
[0049] Figure 4 This is a 3D laser microscopic cross-sectional analysis diagram of the barrier film set of Example 3.
[0050] Icons: 10-first barrier film group; 110-first double-sided barrier film; 112-first back coating layer; 114-first substrate layer; 116-first barrier coating layer; 120-first single-sided barrier film; 122-third substrate layer; 124-third barrier coating layer; 20-second barrier film group; 210-second double-sided barrier film; 212-second back coating layer; 214-second substrate layer; 216-second barrier coating layer; 220-second single-sided barrier film; 222-fourth substrate layer; 224-fourth barrier coating layer; 30-quantum dot adhesive layer; 40-first bonding adhesive layer; 50-second bonding adhesive layer. DETAILED DESCRIPTION
[0051] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0052] Hereinafter, the terms "including", "having" and their cognates, which may be used in various embodiments of the present invention, are intended only to indicate specific features, numbers, steps, operations, elements, components or combinations of the foregoing items, and should not be understood as first excluding the existence of one or more other features, numbers, steps, operations, elements, components or combinations of the foregoing items or adding the possibility of one or more features, numbers, steps, operations, elements, components or combinations of the foregoing items.
[0053] A first aspect of the present invention provides a barrier film, including a single-sided barrier film and / or a double-sided barrier film;
[0054] The single-sided barrier film comprises a substrate and a barrier coating located on one surface of the substrate;
[0055] The double-sided barrier film comprises a substrate, a barrier coating layer located on one surface of the substrate, and a back coating layer located on the other surface of the substrate.
[0056] The barrier film provided by the present invention has stronger barrier properties. Without affecting other properties, it can reduce the problem of local failure caused by scratches on the barrier film during the production process of the quantum dot film, and eliminate the pinhole failure problem caused by the atomic arrangement of the coating. The overall barrier performance is improved, the protection of quantum dots is enhanced, and the service life is extended.
[0057] Furthermore, the barrier coating or the back coating is obtained by PVD or CVD.
[0058] Furthermore, the substrate includes polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polymethyl methacrylate, polylactic acid or polyester polyurethane, preferably polyethylene terephthalate.
[0059] Preferably, the material of the barrier coating includes at least one of SiOx, SiNx, SiCx and ZrOx, wherein 0<x<2.
[0060] Figure 1 This is the structure diagram of α-quartz SiOx. Figure 2 This is the structure diagram of β-quartz SiOx.
[0061] Preferably, the back coating layer is formed by coating with back glue.
[0062] Preferably, the back-coated glue includes resin and organic / inorganic particles.
[0063] Preferably, the resin comprises UV type acrylic resin.
[0064] Furthermore, the thickness of the substrate is 12 to 150 μm. Typically but not limiting, the thickness of the substrate can be, for example, 12 μm, 25 μm, 50 μm, 75 μm, 100 μm, 125 μm or 150 μm, or any value within the range of 12 μm to 150 μm.
[0065] Preferably, the thickness of the barrier coating is 100-200 nm. Typically but not limiting, the thickness of the barrier coating may be, for example, 100 nm, 120 nm, 140 nm, 160 nm, 180 nm or 200 nm, or any value within the range of 100 nm to 200 nm.
[0066] Preferably, the thickness of the back coating layer is 2-10 μm. Typically but not limiting, the thickness of the back coating layer may be, for example, 2 μm, 4 μm, 6 μm, 8 μm or 10 μm, or any value within the range of 2 μm to 10 μm.
[0067] A second aspect of the present invention provides a quantum dot film, comprising a first barrier film group, a quantum dot glue layer and a second barrier film group which are stacked in sequence.
[0068] The first barrier film group and the second barrier film group include at least one layer of the barrier film.
[0069] The quantum dot film provided by the present invention, in view of the advantages of the above barrier film, enables the prepared quantum dot film to have a longer service life and performance stability. This technical solution enables the quantum dot film to have significant application advantages and broad market prospects in the field of display technology.
[0070] Furthermore, the quantum dot glue layer contains quantum dots.
[0071] Preferably, the quantum dots include red quantum dots and green quantum dots.
[0072] Furthermore, the absorption wavelength of the red quantum dots is 620-634 nm, preferably 628 nm.
[0073] Preferably, the absorption wavelength of the green quantum dots is 528-539 nm, preferably 532 nm.
[0074] Furthermore, the first barrier film group includes a double-sided barrier film and a single-sided barrier film.
[0075] Preferably, the number of layers of the single-sided barrier film is 0 to 3.
[0076] Preferably, the double-sided barrier film is located at the outermost side of the first barrier film group.
[0077] Furthermore, the second barrier film group includes a double-sided barrier film and a single-sided barrier film.
[0078] Preferably, the number of layers of the single-sided barrier film is 0 to 3.
[0079] Preferably, the double-sided barrier film is located at the outermost side of the second barrier film group.
[0080] In one embodiment of the present invention, the schematic diagram of the structure of the quantum dot film is as follows Figure 3 As shown, it includes a first barrier film group 10 , a second barrier film group 20 and a quantum dot glue layer 30 .
[0081] The first barrier film set 10 includes a first double-sided barrier film 110 and a first single-sided barrier film 120 , and the first double-sided barrier film 110 and the first single-sided barrier film 120 are bonded together via a first bonding adhesive layer 40 .
[0082] The first double-sided barrier film 110 includes a first back coating layer 112 , a first substrate layer 114 , and a first barrier coating layer 116 which are sequentially stacked. The first single-sided barrier film 120 includes a third substrate layer 122 and a third barrier coating layer 124 .
[0083] The second barrier film set 20 includes a second double-sided barrier film 210 and a second single-sided barrier film 220 . The second double-sided barrier film 210 and the second single-sided barrier film 220 are bonded together via a second bonding adhesive layer 50 .
[0084] The second double-sided barrier film 210 includes a second back coating layer 212 , a second substrate layer 214 , and a second barrier coating layer 216 stacked in sequence. The second single-sided barrier film 220 includes a fourth substrate layer 222 and a fourth barrier coating layer 224 .
[0085] The third aspect of the present invention provides a method for preparing the quantum dot film, comprising the following steps:
[0086] A. Use a bonding adhesive to bond the barrier films in the first barrier film group and the second barrier film group together, and after curing, obtain the first barrier film group and the second barrier film group respectively.
[0087] B. Applying quantum dot glue between the first barrier film group and the second barrier film group, and UV curing to obtain the quantum dot film.
[0088] The method for preparing the quantum dot film provided by the invention has simple process, high mechanization degree and is suitable for large-scale industrial production.
[0089] Furthermore, the bonding adhesive includes UV bonding adhesive, thermosetting bonding adhesive or mixed bonding adhesive, preferably thermosetting bonding adhesive.
[0090] Preferably, the lamination method includes roller lamination.
[0091] Preferably, in step B, the coating method is slit coating.
[0092] Preferably, in step B, during the UV curing, the energy is 150-600 mj / cm.
[0093] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0094] Example 1
[0095] This embodiment provides a barrier film set, which is composed of a single-sided barrier film and a non-coated PET. The thickness of the single-sided barrier film is 12 μm, the thickness of the barrier coating is 100 nm, and the thickness of the non-coated PET is 75 μm.
[0096] The single-sided barrier film and the uncoated PET were laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set with a total thickness of 100 μm.
[0097] Example 2
[0098] This embodiment provides a barrier film set, which is composed of a single-sided barrier film and a non-coated PET. The thickness of the single-sided barrier film is 12 μm, the thickness of the barrier coating is 100 nm, and the thickness of the non-coated PET is 75 μm.
[0099] The single-sided barrier film and the uncoated PET were laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set with a total thickness of 100 μm.
[0100] Example 3
[0101] This embodiment provides a barrier film set, which is composed of two layers of single-sided barrier films.
[0102] In one single-sided barrier film, the base layer thickness is 12 μm and the coating thickness is 100 nm. In another single-sided barrier film, the base layer thickness is 75 μm and the coating thickness is 150 nm.
[0103] The coated PET is laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set with a total thickness of 100 μm.
[0104] Example 4
[0105] This embodiment provides a barrier film set, which is composed of two layers of single-sided barrier films.
[0106] In one single-sided barrier film, the base layer thickness is 12 μm and the coating thickness is 150 nm. In another single-sided barrier film, the base layer thickness is 75 μm and the coating thickness is 100 nm.
[0107] The coated PET is laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set with a total thickness of 100 μm.
[0108] Example 5
[0109] This embodiment provides a barrier film set, which is composed of three layers of single-sided barrier films.
[0110] In two layers of single-sided barrier films, the base layer thickness is 12 μm and the coating thickness is 100 nm. In another layer of single-sided barrier film, the base layer thickness is 75 μm and the coating thickness is 100 nm.
[0111] The coated PET was laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set with a total thickness of 112 μm.
[0112] Example 6
[0113] This embodiment provides a barrier film set, which is composed of three layers of single-sided barrier films.
[0114] In one of the single-sided barrier films, the base layer thickness is 12 μm and the coating thickness is 100 nm. In the other two single-sided barrier films, the base layer thickness is 75 μm and the coating thickness is 100 nm.
[0115] The coated PET is laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set.
[0116] Comparative Example 1
[0117] Compared with Example 1, the single-sided 12 μm coated PET is replaced with a double-sided coated PET.
[0118] 1 layer of double-sided coated barrier film with a thickness of 12μm, 1 layer of uncoated barrier film with a coating thickness of 100nm and a thickness of 75μm.
[0119] The coated PET is laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set with a total thickness of 100 μm.
[0120] Comparative Example 2
[0121] 1 layer of double-sided coated barrier film with a thickness of 12μm, 1 layer of uncoated barrier film with a coating thickness of 150nm and a thickness of 75μm.
[0122] The coated PET is laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set with a total thickness of 100 μm.
[0123] Comparative Example 3
[0124] Compared with Example 1, the single-sided 75 μm uncoated PET is replaced with double-sided coated PET.
[0125] One layer of single-sided coated barrier film with a thickness of 12μm and a coating thickness of 100nm, and one layer of double-sided coated barrier film with a thickness of 75μm and a coating thickness of 100nm.
[0126] The coated PET is laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set with a total thickness of 100 μm.
[0127] Comparative Example 4
[0128] One layer of single-sided plated barrier film with a thickness of 12μm and a coating thickness of 100nm, and one layer of double-sided plated barrier film with a thickness of 75μm and a coating thickness of 150nm.
[0129] The coated PET is laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set with a total thickness of 100 μm.
[0130] Comparative Example 5
[0131] Compared with Example 1, the single-sided 12 μm coated PET and the single-sided 75 μm uncoated PET are replaced with double-sided coated PET.
[0132] One layer of barrier film coated on both sides with a thickness of 12μm and a coating thickness of 100nm; one layer of barrier film coated on both sides with a thickness of 75μm and a coating thickness of 100nm.
[0133] The coated PET is laminated with a laminating adhesive using a laminating roller and baked at 85° C. for 2-3 minutes to obtain a barrier film set with a total thickness of 100 μm.
[0134] Test Example 1
[0135] The barrier film groups obtained in the examples and comparative examples were subjected to the following tests.
[0136] Oxygen permeability test: Adopt the standard: GB / T21529 test, the smaller the value, the better.
[0137] Water vapor transmission rate test: Adopt the standard: GB / T1038-1500 test, the smaller the value, the better.
[0138] Backlight observation: 32-inch side-entry backlight to observe the film surface with naked eyes;
[0139] Brightness test: CS1500 spectrophotometer.
[0140] Reliability optical test: The manufactured quantum dot film has a structure similar to a sandwich structure with the upper and lower finished water and oxygen barrier films wrapping the middle quantum dot glue layer; it is placed in an 85℃ / 85%RH environment, and the initial and 1000H optical data are tested. The protection of the quantum dot life span is judged by the △1000H optical change value.
[0141] The test results are shown in Table 1.
[0142] Table 1
[0143]
[0144] As can be seen from Table 1, the coating on one or two PET sheets provided by the present invention and combining them into a complete barrier film has stronger barrier properties. Without affecting other properties, it can reduce the problem of local failure caused by scratching of the barrier film in the production process of the quantum dot film, and eliminate the problem of pinhole failure caused by the arrangement of the atoms in the coating, while improving its service life; among Examples 1 and 2, and Examples 3 and 4, the data of Example 3 is the best, indicating that increasing the coating PET has an improvement effect, and increasing the coating thickness also has an effect, but increasing the coating thickness on thinner PET will have a counter-effect. In Examples 5 and 6, the barrier effect of water and oxygen is no longer increased by increasing the number of coated PET sheets, and the optical attenuation is more, which may be affected by the increase in the number of bonding layers. In Comparative Examples 1 and 2, adding multiple coatings and thicknesses on thin PET will make the situation worse. In Comparative Examples 3 and 4, adding multiple coatings and thicknesses on thick PET has a good effect on water and oxygen barrier films, but the optics are poor, and the substrate may be denatured after multiple processing. In Comparative Example 5, the substrate has worse water and oxygen barrier and optical data after multiple coating processes and multiple laminations. Therefore, it is not the case that the more coatings, the better, the thicker the coatings, the better, and the more laminations, the better. Example 2 is the best solution.
[0145] Characterization Example 1
[0146] The barrier film set of Example 3 was subjected to 3D laser microscopic cross-sectional analysis to obtain the following image: Figure 4 As shown, from Figure 4 It can be seen that the finished barrier film has a multi-layer structure, which is composed of 12um PET with a coating and 75um PET with a coating from top to bottom, and the bottom layer is the back coating layer in an uneven state.
[0147] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A barrier film, characterized in that: Including single-sided barrier film and / or double-sided barrier film; The single-sided barrier film comprises a substrate and a barrier coating located on one surface of the substrate; The double-sided barrier film comprises a substrate, a barrier coating layer located on one surface of the substrate, and a back coating layer located on the other surface of the substrate.
2. The barrier film according to claim 1, characterized in that The substrate includes polyethylene terephthalate, polyethylene naphthalate, polycarbonate, polymethyl methacrylate, polylactic acid or polyester polyurethane, preferably polyethylene terephthalate; Preferably, the material of the barrier coating includes at least one of SiOx, SiNx, SiCx and ZrOx, wherein 0<x≤2; Preferably, the back coating layer is formed by coating with back glue; Preferably, the back-coated glue includes resin and organic / inorganic particles; Preferably, the resin comprises UV type acrylic resin.
3. The barrier film according to claim 1, characterized in that The thickness of the substrate is 12 to 150 μm; Preferably, the thickness of the barrier coating is 100-200 nm; Preferably, the back coating layer has a thickness of 2 to 10 μm.
4. A quantum dot film, characterized in that: It includes a first barrier film group, a quantum dot glue layer and a second barrier film group which are stacked in sequence; The first barrier film group and the second barrier film group include at least one layer of the barrier film according to any one of claims 1 to 3.
5. The quantum dot film according to claim 4, characterized in that: The quantum dot glue layer contains quantum dots; Preferably, the quantum dots include red quantum dots and green quantum dots.
6. The quantum dot film according to claim 5, characterized in that: The wavelength of the red quantum dots is 620-634 nm; Preferably, the wavelength of the green quantum dots is 528-539 nm.
7. The quantum dot film according to claim 4, characterized in that: The first barrier film group includes a double-sided barrier film and a single-sided barrier film; Preferably, the number of layers of the single-sided barrier film is 0 to 3; Preferably, the double-sided barrier film is located at the outermost side of the first barrier film group.
8. The quantum dot film according to claim 4, characterized in that: The second barrier film group includes a double-sided barrier film and a single-sided barrier film; Preferably, the number of layers of the single-sided barrier film is 0 to 3; Preferably, the double-sided barrier film is located at the outermost side of the second barrier film group.
9. A method for preparing a quantum dot film according to any one of claims 4 to 8, characterized in that: The following steps are involved: A. Using a bonding adhesive to bond the barrier films in the first barrier film group and the second barrier film group together, and after curing, the first barrier film group and the second barrier film group are obtained respectively; B. Applying quantum dot glue between the first barrier film group and the second barrier film group, and UV curing to obtain the quantum dot film.
10. The preparation method according to claim 9, characterized in that: The bonding adhesive includes UV bonding adhesive, thermosetting bonding adhesive or mixed bonding adhesive, preferably thermosetting bonding adhesive; Preferably, the lamination method includes roller lamination; Preferably, in step B, the coating method is slit coating; Preferably, in step B, during the UV curing, the energy is 150-600 mj / cm.